Rat rotator cuff muscle responds differently from hindlimb muscle to a combined tendon‐nerve injury. Issue 7 (13th May 2015) - Davies, Michael R.; Ravishankar, Bharat; Laron, Dominique; Kim, Hubert T.; Liu, Xuhui; Feeley, Brian T.
ABSTRACT Rotator cuff tears (RCTs) are among the most common musculoskeletal injuries seen by orthopaedic surgeons. Clinically, massive cuff tears lead to unique pathophysiological changes in rotator cuff muscle, including atrophy, and massive fatty infiltration, which are rarely seen in other skeletal muscles. Studies in a rodent model for RCT have demonstrated that these histologic findings are accompanied by activation of the Akt/mammalian target of rapamycin (mTOR) and transforming growth factor‐β (TGF‐β) pathways following combined tendon‐nerve injury. The purpose of this study was to compare the histologic and molecular features of rotator cuff muscle and gastrocnemius muscle—a major hindlimb muscle, following combined tendon‐nerve injury. Six weeks after injury, the rat gastrocnemius did not exhibit notable fatty infiltration compared to the rotator cuff. Likewise, the adipogenic markers SREBP‐1 and PPARγ as well as the TGF‐β canonical pathway were upregulated in the rotator cuff, but not the gastrocnemius. Our study suggests that the rat rotator cuff and hindlimb muscles differ significantly in their response to a combined tendon‐nerve injury. Clinically, these findings highlight the unique response of the rotator cuff to injury, and may begin to explain the poor outcomes of massive RCTs compared to other muscle‐tendon injuries. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1046–1053, 2015.